Variation in Management of CKD-Associated Pruritus: Results From a Multinational Survey of Kidney Units - Sreeram Venugopal; Daniel V. O’Hara; Neeru Agarwal; Barnaby D. Hole; Charlotte M. Snead; Elizabeth Stallworthy; Fergus J. Caskey; Kathryn Ducharlet; Brendan Smyth (Kidney Medicine, 2025)
Rationale & Objective: Chronic kidney disease-associated pruritus (CKDaP) is a distressing symptom affecting a significant proportion of people with advanced kidney disease. There are many studies of varying quality in the literature testing a wide variety of CKDaP therapies and no evidence-based consensus guidelines for management. We aimed to describe the breadth of treatments in use for CKDaP in real-world practice. Study Design: A cross-sectional online survey. Setting & Participants: Kidney care units in Australia, New Zealand (NZ), and the United Kingdom (UK). Surveyed from April 2022, to December 2022. Outcomes: Usage of 28 CKDaP therapies (excluding emollients/moisturizers) was categorized as “first-line,” “second-line,” “refractory symptoms only,” “rarely used,” or “never used.” Analytical Approach: Descriptive analysis with differences between categories assessed by Fisher exact test. Results: One hundred four responses were received from 171 contacted kidney units (Australia 51 [49%], NZ 6 [6%], and UK 47 [45%]) with an overall response rate of 61%. Including ''other'' responses, 35 treatments were in first-line or second-line use. Gabapentinoids (gabapentin or pregabalin) were the most widely used first-line systemic agent (49 units [47%]), followed by antihistamines (27 [26%]). Menthol was the predominant first-line topical agent (41, [39%]). Significant inter-country disparities were noted: doxepin, evening primrose oil, sertraline, and topical γ-linolenic acid were more frequently used in Australia than in NZ, and the UK, whereas hydroxyzine was preferentially used in UK units (P < 0.05). Units with a kidney supportive care service were more likely to use gabapentinoids, 5-hydroxytryptamine3 receptor antagonists, hydroxyzine, and topical therapies, and less likely to use promethazine (P < 0.05). Limitations: Difelikefalin was not widely available during the survey period, which may limit generalizability. Conclusions: There is considerable variation in the management of CKDaP. Unexplained clinical variation suggests a need for the development of evidence-based guidelines and additional high-quality studies to inform care. Plain-Language Summary: People with chronic kidney disease often experience severe itching, which can significantly affect their well-being. There's no clear consensus on the best approach. This study surveyed 104 kidney care units in Australia, New Zealand, and the United Kingdom to understand how they treat this condition in practice. More than 35 different treatments were in use as first-line or second-line therapies with wide variation in treatment approaches both between units and countries. The 3 most commonly used first-line therapies were gabapentinoids, antihistamines, and topical menthol, and no therapy was first-line at a majority of units. This variation in practice suggests a need for better evidence and guidelines to ensure all patients receive the most effective care for pruritus.